English Educational Game Modeling Using Goal Directed Design Method - Lupita, Maria; Ambarwati, Theresia (Universitas Amikom Purwokerto, 2024)
Language and Communication Development. Through play, children engage in conversation, listen to stories, and communicate with others. This enriches their vocabulary and helps them understand the structure of language. Early literacy is essential to early childhood learning. Playing with letters, words, and picture books helps children develop early literacy skills that are essential for later academic success. A learning aid in the media is an educational game. In this study, we developed an English vocabulary learning application for fruit and animal names. The application is used by kids between the ages of 4 and 6. The goal of this research is to create an application that will help kids recall things better and expand their vocabulary. We employ the Goal Directed Design Method for the design of the user interface. The research, modelling, requirements, definition, framework definition, refinement, and support are the eight primary stages of this method. Eighteen youngsters between the ages of four and six participated in this study. According to the application's evaluation, all participants were able to recall fruit and animal names with an approximate 10% increase.